Pengaruh Penerapan Model Pembelajaran PBL Pada Mata Pelajaran IPAS Terhadap Hasil Belajar Peserta Didik Kelas V SDN 06 Pontianak Selatan - Rizka Dwi Yanti; Kartono Kartono; Dyoty Auliya Vilda Ghasya (Journal on Education, 2024)
This research aims to determine the effect of implementing the Problem Based Learning model in science subjects on the learning outcomes of class V students at SDN 06 South Pontianak. The research method used is an experiment in the form of a quasi-experimental design, a nonequivalent control group design. The population in this study was all class V students at SDN 06 South Pontianak, class VA totaling 28 students and class VB totaling 29 students. The sample was determined using nonprobability sampling, a saturated sampling type. Data collection techniques use measurement techniques. The instrument used is a learning outcomes test in the form of multiple choice with 30 questions. Based on the calculation of the hypothesis test, tcount is 2,648 with a ttable of 1,864, because tcount > ttable then Ha is accepted. Proves that there is an influence of implementing the PBL learning model. The results of the effect size calculation were obtained at 0,50, including the medium criteria, so it can be concluded that the PBL learning model in science subjects has a moderate influence on the learning outcomes of class V students at SDN 06 South Pontianak.